A QSAR model for predicting antidiabetic activity of dipeptidyl peptidase-IV inhibitors by enhanced binary gravitational search algorithm. Issue 6 (3rd June 2019) - Al-Fakih, A.M.; Algamal, Z.Y.; Lee, M.H.; Aziz, M.; Ali, H.T.M.
ABSTRACT: Time-varying binary gravitational search algorithm (TVBGSA) is proposed for predicting antidiabetic activity of 134 dipeptidyl peptidase-IV (DPP-IV) inhibitors. To improve the performance of the binary gravitational search algorithm (BGSA) method, we propose a dynamic time-varying transfer function. A new control parameter, μ, is added in the original transfer function as a time-varying variable. The TVBGSA-based model was internally and externally validated based on Q int 2, Q L G O 2, Q B o o t 2, M S E t r a i n, Q e x t 2, M S E t e s t, Y-randomization test, and applicability domain evaluation. The validation results indicate that the proposed TVBGSA model is robust and not due to chance correlation. The descriptor selection and prediction performance of TVBGSA outperform BGSA method. TVBGSA shows higher Q int 2 of 0.957, Q L G O 2 of 0.951, Q B o o t 2 of 0.954, Q e x t 2 of 0.938, and lower M S E t r a i n and M S E t e s t compared to obtained results by BGSA, indicating the best prediction performance of the proposed TVBGSA model. The results clearly reveal that the proposed TVBGSA method is useful for constructing reliable and robust QSARs for predicting antidiabetic activity of DPP-IV inhibitors prior to designing and experimental synthesizing of new DPP-IV inhibitors.